Progress, Challenges, and Future Prospects of Dengue Vaccine: A Comprehensive Review (Bangladesh Journal of Medical Microbiology, 2026)
Dengue fever, caused by the dengue virus (DENV), is a reemerging global health concern transmitted by Aedes mosquitoes associated with high mortality in the present situation. DENV comprises four distinct serotypes (DENV-1, -2, -3, and -4) with shared genetic elements, but infection with different serotypes enhances the risk of severe dengue. DENV-2 and DENV-3 are prominent in global infections. Accurate diagnosis is crucial for treatment, surveillance, and vaccine research. Immune responses, especially cross-reactive immunity, play a pivotal role in dengue pathogenesis, potentially contributing to severe manifestations. Several dengue vaccines have been developed to combat this viral disease. Due to safety concerns, the first dengue vaccine, Dengvaxia (Sanofi Pasteur's live-attenuated tetravalent vaccine), is only advised for those who have already had dengue. Since 2024, the World Health Organization has prequalified a second vaccine, Qdenga (TAK-003), created by Takeda. It targets all four serotypes, is administered in two doses spaced three months apart, and can be used in high-transmission areas on children aged 6 to 16. However, dengue vaccines face unique challenges. Ensuring that the vaccine provides balanced protection against all serotypes is crucial. This led to changes in vaccine recommendations and emphasized the importance of accurately diagnosing prior dengue exposure. Research and development of dengue vaccines continue to address these complexities and improve their effectiveness and safety. Dengue vaccination remains an important strategy in preventing this mosquito-borne viral disease, especially in regions where dengue is endemic like Bangladesh.Bangladesh Journal of Medical Microbiology, July 2025;19 (2):143-153